Waste Charity: Climate Change Mitigation Efforts and Green Economic Sustainability - Muhammad Zainul Abidin; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The increasing volume of waste has become a significant challenge in efforts to maintain environmental sustainability. This article proposes the concept of